BİLATERAL PLEVRA VE PERİKARD SIVISI OLAN BİR BEHÇET HASTALIĞI OLGUSU - SOY, Mehmet; ÖZBEK, Süleyman; CANATAROĞLU, Abdullah; ERKEN, Eren (Cerrahpaşa Medical Journal, 2014)
Background and Observation. Behçet's syndrome is a primary vasculitis. In addition to mucocutaneous; ophthalmic and musculoskeletal symptoms, rarely pleural and pericardial fluid is reported in Behçet's patients due to thrombosis of superior vena cava. Here in we report a patient with Behçet's syndrome, who had superior vena cava syndrome that caused pericardial and pleural effision, and due to resistance to medical therapy, unilateral pleurodesis with bleomycin solution then was performed.